Address to the United Nations Conference on the Human Environment, Stockholm, June 8, 1972 - McNamara, Robert S. (World Bank, Washington, DC, 2020)
Robert S. McNamara, President of the World Bank Group, says the relationship between two fundamental requirements need to be examined: the necessity for economic development; and the preservation of the environment. He outlines the steps the Bank is taking to deal with the ramifications of that relationship and illustrates practical measures that are proving to be both feasible and effective. He suggests the most useful direction for the international development community is to assist in the economic advance of the developing countries while responsibly preserving and enhancing the environment. He points out that the broad statistical evidence is clear that there is dangerously skewed distribution of income both within developing nations, and between the collectively affluent and the collectively indigent nations. He reemphasizes that development cannot succeed unless that massively distorted distribution of income is brought into a reasonable balance. He also suggests that what is needed is the close cooperation of economists and ecologists, of social and physical scientists, of experienced political leaders and development project specialists. He briefs about five essential requirements to assist in preserving and enhancing the environment. First, recognize that economic growth in the developing countries is essential if they are to deal with their human problems. Second, act on the evidence that such growth need not cause unacceptable ecological penalties. Third, assist the developing countries in their choice of a pattern of growth which will yield a combination of high economic gain with low environmental risk. Fourth, provide external support required for that economic advance by moving more rapidly toward meeting the United Nations concessionary aid target and by dismantling and discarding inequitable trade barriers which restrict exports from poorer countries. Fifth, realize that human degradation is the most dangerous pollutant there is. He says that the impetus for this conference is respect for man and his home and that respect can be translated into practical action. The leading edge of that action is to protect man from the one hazard which can injure not only his habitat and his health, but his spirit as well. He concludes that poverty is cruel and senseless, but curable. The task, he urges, is not to create an idyllic environment peopled by the poor, but to create a decent environment peopled by the proud.